1989
DOI: 10.1007/bf02370276
|View full text |Cite
|
Sign up to set email alerts
|

Use of pesticides for mass production of vesicular-arbuscular mycorrhizal inoculum

Abstract: Nine fungicides, 3 nematicides and 5 insecticides/acaricides were incorporated into the pot cultures of the VAM fungus Glomus fasciculatum in order to study their effect on the mycorrhizal association and the contaminant organisms. All the pesticides were found to be deleterious to VAM at the recommended level. Captan and carbofuran, at half the recommended level (125mg and 144.5mg respectively/2.5 litre of the substrate mix), increased significantly the percentage root colonization, extra-matrical chlamydospo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…Experiments with Copper oxychloride reported negative effects for Glomus sp. and Arachis hypogea L. (Sreenivasa and Bagyaraj, 1989) and neutral effects for Glomus fasciculatum and Agrostis palustris L. (Rhodes and Larser, 1981), thus results were dependent on the crop and the AMF involved.…”
Section: Discussionmentioning
confidence: 94%
“…Experiments with Copper oxychloride reported negative effects for Glomus sp. and Arachis hypogea L. (Sreenivasa and Bagyaraj, 1989) and neutral effects for Glomus fasciculatum and Agrostis palustris L. (Rhodes and Larser, 1981), thus results were dependent on the crop and the AMF involved.…”
Section: Discussionmentioning
confidence: 94%
“…In the previous studies it was reported that the application of fungicides inhibited the development of AMF symbioses. For example, Sreenivasa and Bagyaraj (1989) found a reduction in root colonization by AMF and spore production by copper oxychloride and Carbofuran. As a non-selective fungicide chlorothalonil has the potential to inhibit the growth of AMF indicating the percentage of colonization was significantly decreased with increasing chlorothalonil concentration.…”
Section: Discussionmentioning
confidence: 99%
“…AM-fungi are known to be effective in increasing phosphorus uptake in many crops, particularly in low phosphorus soils (Osonubi et al, 1991). They are associated with improved growth of many plant species due to increased nutrient uptake, production of growth promoting substances, tolerance to drought and synergistic interaction with other beneficial soil micro-organisms such as N-fixers and P-solubilizers (Sreenivasa and Bagyaraj, 1989). Arbuscular mycorrhizal fungi play an important role in sustainable agriculture as well as agricultural ecosystem management.…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%